PERBANDINGAN PEMBERIAN IKAN GABUS DAN TELUR AYAM TERHADAP PENYEMBUHAN LUKA PASCA BEDAH POST SECTIO CEASEREA - Dian Zuiatna; Putri Diah Pemiliana; Saskiyanto Manggabarani (Universitas Prima Indonesia, 2021)
The incidence of sectio caesarea in Indonesia according to national survey data in 2016 is 912,000 out of 4,039,000 deliveries or around 22.8% of all deliveries. Delivery by cesarean section of the risk of death is 25 times greater and the risk of infection is 80 times higher than that of vaginal delivery. The most important requirement that must be met by post partum mothers with sectio cesarean wounds is good nutrition for the immune system and wound healing because there are several nutrients that are needed to support the body's immune system and play an important role in the wound healing process. The aim of this research is to test the effectiveness of protein diet in wound healing in post-op women with caesarean section which is applied in health care facilities and in patient homes. This type of research was observational with a Quasi experiment design, namely post test only with control group design. This research will be conducted in Binjai City, patients who are discharged from Artha Medica Hospital in 2020. The sample of this study is a post partum section of the ceaserea mother who has the same characteristics and the location is in the Binjai City area and has never been given protein diet consumption. The sampling technique was selected by consecutive sampling method consisting of the intervention group and the control group. Data were analyzed by univariate and bivariate analysis with T Test Sample. Based on the results of the study, it was obtained a p value of 0.000 <0.05, which indicates that there is a difference in the consumption of a high protein diet on the post-sectio ceaserea wound healing process.